BOARD OF DIRECTORS' TENDENCIES TOWARD PROFITABILITY AND ENVIRONMENTAL PERFORMANCE IN INDONESIA - yessica step; Muhammad Taufik (Universitas Internasional Batam, 2024)
This study investigates the impact of board diversity on profitability and environmental performance. The PROPER ratings are designed to address the shortcomings in corporate social responsibility (CSR) disclosures. Moreover, Tobin's Q and business volume ensure consistency in sales and market performance. Consequently, this study contributes to understanding directors' tendency to profitability and/ or environmental concerns, resulting in tremendous corporate governance literature. BOD diversity includes gender, age, education level, expertise, and nationality. In total, 272 data were analysed in the panel data test from 68 companies in 2017-2020. There is a homogeneous composition of the board, which consists mostly of men, older people, bachelor's degrees, and locals. However, BOD expertise is quite heterogeneous. The presence of male and local directors can improve financial performance, but they delegitimise the environment. The old directors cause Tobin's Q to decline, and vice versa for local directors, but they are apathetic to the environment. Surprisingly, board education level improves environmental performance, while accounting expertise has the opposite effect, but they adversely affect financial performance. To attain Sustainable Development Goal No. 5 gender equality, the government must intervene in regulations while companies accommodated. The complex business, including profit and environmental performance, demonstrates the strategic importance of accounting expertise; hence, their proportion needs to be increased. Additionally, homogeneity affects performance stagnation; thus, younger, higher education (master) levels and more foreign directors need to be increased.